MAJAS DAN MAKNA PADA LIRIK LAGU NADIN AMIZAH YANG BERJUDUL “SEPERTI TULANG” - Fitri, Nur (IKIP Siliwangi, 2020)
This research is motivated by the rise of song lyrics whose meaning is already immoral. Some of the song lyrics even have meaning that is not appropriate. The purpose of this article is to analyze the composition and meaning contained in the lyrics of the Nadin Amizah song entitled seperti tulang. Researches are interested in analyzing song seperti tulang because in them there are special and beautiful words and meaning that can be learned. In addition, researches are also interested in knowing what kind of content is contained in the lyrics of the song, because in the lyrics of this song the meaning or hope to be conveyed. Then the method used in this research is descriptive qualitative, a method by analyzing the data and the result of the data then processed in the form of a description. The subject analyzed was song lyrics seperti tulang. The result of the analysis of the lyrics of this song is that there is personification, rhetoric, and paradoxical cooperation. The meaning and message contained in the lyrics of this song is the story of human being who is good at hiding wounds even though he is often seen laughing.